Systemic Design Theory, Methods, and Practice (Translational Systems Sciences,, 2018)
This book presents emerging work in the co-evolving fields of design-led systemics, referred to as systemic design to distinguish it from the engineering and hard science epistemologies of system design or systems engineering. There are significant societal forces and organizational demands impelling the requirement for "better means of change" through integrated design practices of systems and services. Here we call on advanced design to lead programs of strategic scale and higher complexity (e.g., social policy, healthcare, education, urbanization) while adapting systems thinking methods, creatively pushing the boundaries beyond the popular modes of systems dynamics and soft systems. Systemic design is distinguished by its scale, social complexity and integration - it is concerned with higher-order systems that that entail multiple subsystems. By integrating systems thinking and its methods, systemic design brings human-centred design to complex, multi-stakeholder service systems. As designers engage with ever more complex problem areas, it is necessary to draw on a basis other than individual creativity and contemporary "design thinking" methods. Systems theories can co-evolve with a new school of design theory to resolve informed action on today's highly resilient complex problems and can deal effectively with demanding, contested and high-stakes challenges.